A Spatial Perspective on European Integration: Heterogeneous Welfare and Migration Effects from the Single Market and the Brexit - Marcel Henkel; Tobias Seidel (Center for Economic Studies and ifo Institute (CESifo), 2016)
We use a quantitative model to study the implications of European integration for welfare and migration flows across 1,318 regions. The model suggests that an increase of trade barriers to the level of 1957 reduces welfare by about 1-2 percent on average, depending on the presumed trade elasticity. However, remote regions may face initial welfare losses of up to 4 percent causing an estimated migration of about 8 million individuals to the European core. This implies that the dismantling of trade barriers in Europe has led to a more homogeneous spatial distribution of economic activity. With regard to the Brexit, we find moderate welfare losses for the UK of -0.44 percent in the most pessimistic scenario while continental Europe's welfare declines by 0.18 percent. In the most unfavorable scenario, about 500,000 people would leave the UK in the long run.
Keywords: F10; F12; F15; R11; R12; R13; R23; 330; regional integration; labor mobility; spatial inequality